2022
DOI: 10.5334/ijic.6472
|View full text |Cite
|
Sign up to set email alerts
|

Social Prescribing: Systematic Review of the Effectiveness of Psychosocial Community Referral Interventions in Primary Care

Abstract: Introduction: Social prescribing (SP) aims to provide targeted psychosocial support and close the gap between medical and non-medical services. This review assesses the effectiveness of community-based SP interventions. Methods:We performed a systematic review and qualitative synthesis of interventional studies of community referral interventions focused on facilitating psychosocial support. We considered health-related endpoints, other patient reported outcomes, or health care utilization. Six databases, grey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 53 publications
3
24
0
1
Order By: Relevance
“…Our study resonates with preceding SP reviews regarding the limitations in the available evidence and the need for further high-quality research 23 24 26 29 34 76–78. As we envisioned, there is limited development and evaluation of SP interventions to address the chronic disease risk factors in adults.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our study resonates with preceding SP reviews regarding the limitations in the available evidence and the need for further high-quality research 23 24 26 29 34 76–78. As we envisioned, there is limited development and evaluation of SP interventions to address the chronic disease risk factors in adults.…”
Section: Discussionsupporting
confidence: 71%
“…Findings from the present review and numerous SP reviews of other health outcomes23 24 26 27 29 30 33 35 36 76 81 have clearly shown that the evidence was still insufficient and scientifically inconclusive to justify the recommendation reliably. Some immediate increases in physical activity and energy expenditure are noted in our study, but whether the benefits sustain post-trial is questionable.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Research on the effectiveness of SP is emerging and remains equivocal (Bickerdike et al, 2017;Kimberlee, 2015;Napierala et al, 2022;O'Sullivan et al, 2022). Existing studies evaluating SP interventions have been criticized for their methodological limitations (Kiely et al, 2021;Kimberlee, 2015).…”
Section: Limitations Of the Social Prescribing Researchmentioning
confidence: 99%
“…Whilst there is considerable evidence to support the use of SP 4,5 , a common criticism is a lack of robust evidence on its effectiveness [6][7][8][9][10] . SP has been suggested as a tool to reduce health inequalities by supporting individuals in areas of deprivation [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%